Strategi Komunikasi Digital Dinas Komunikasi, Informatika, dan Statistik DKI Jakarta dalam Penyebaran Informasi Publik melalui Media Sosial Instagram @katakotajakarta - Khansa Deliylah; Hudi Santoso (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the digital communication strategy implemented by the Jakarta Communication, Informatics, and Statistics Office (Diskominfotik) in the dissemination of public information through the @katakotajakarta Instagram account. The research method uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and literature studies. The results of the study show that there is a shift in communication patterns from one direction to a more interactive two-way, characterized by the use of visual content, the use of casual language, and systematic content planning. The use of the Reels feature has proven to be effective in increasing audience reach, especially from non-followers. However, the challenges faced include fluctuations in engagement and the risk of information overload that can reduce the effectiveness of communication. This study concludes that adaptive and data-based digital communication strategies are able to increase the effectiveness of public communication and strengthen the relationship between the government and the community. These findings provide practical implications for the management of public communication in the digital era, especially in utilizing social media as an interactive means that support transparency and public participation.